The light of learning: Hasidism in Poland on the eve of the Holocaust - Dynner, Glenn (Oxford University Press, Incorporated, 2024)
The Light of Learning is a pioneering study that belies notions of late Hasidic decadence and decline, and transforms our understanding of Polish Jewry during its final hour. In interwar Poland, Hasidism underwent a pedagogical revolution. By mobilizing Torah study, Hasidic leaders were able to subvert the "civilizing" projects of the Polish state, challenge the ascendancy of Zionism and Socialism, and create clandestine yeshiva bunkers in Nazi-era ghettos. Hasidic Torah study was thus not only a spiritual-intellectual endeavor but a political practice that fueled a formidable culture of resistance.